Over-exploiting the oceans the dangers of over-fishing - Sanchez Gallo, Jorge; Rodriguez, Chema; Films For The Humanities & Sciences (Firm). (Hamilton, NJ : Films for the Humanities & Sciences, 2008)
How long will the biosphere tolerate exploitation of the oceans? Are local fishermen a doomed species? What can be done to reverse the decline of fish stocks around the planet? This program documents the environmental and socioeconomic costs of excessive foshing, contrasting traditional maritime practices with large-scale fishing off Africa's coasts. Monopolization and the failure of international regulations are crucial topics.
[j.1]. Global dump: toxic waste and the planetary ecosystem -- [j.2]. A world apart: global inequality and its consequences -- [j.3]. Food for all: global agriculture and the developing world -- [j.4]. Who's destroying the forest? A global analysis -- [j.5]. Over-exploiting the oceans: the dangers of over-fishing.
Volume numbers assigned by cataloger in the order of the publisher's item numbers.
DVD format.
Keywords: Fisheries -- Social aspects; Fisheries -- Economic aspects; Fisheries -- Environmental aspects